Development of an Android Application with Self Directed Learning to Improve the Quality and Effectiveness of Arts Learning for Performing Arts Education Students in a Wetland Environment: Lesson from Indonesia - Nurdiyana, Tutung; Indriyani, Putri Dyah; Hikmah, Sherly Nur; Hidayat, Yusuf (Journal of Ecohumanism, 2024)
Learning through technology-assisted media is a solution when the practical learning process requires a long time and there is insufficient time for face-to-face learning. This research intends to develop an Android application containing Self Directed Learning to improve the quality of effectiveness of arts learning for Performing Arts Education students so that students can effectively and independently learn and master practical material techniques in the learning process. This research aims to test the validity, practicality, and effectiveness of teaching materials in the form of an Android application that has self-directed learning content in arts learning. The research method used is Research and Development (R&D) with the ASSURE development model. Validators consist of Anthropology lecturers, Dance Arts lecturers, Music Arts and Performing Arts Education lecturers, FKIP ULM, dance arts teachers, and music arts teachers in the Banjarmasin City area. The practicality of the Android application being developed is reviewed based on aspects of benefits, usability, and time efficiency as measured through student response questionnaires. The effectiveness of the Android application developed is seen from the aspect of achieving students' problem-solving skills through learning outcomes tests.